(untitled) (International Journal of Engineering and Computer Science, 2017)
This paper presents a design of a bandpass filter using combination of a simple transmission line and cylindrical dielectric resonator for wide band application. Four dielectric resonators with same permittivity (FR4 epoxy ) having high permittivity and diameter of 1mm are identified to be contributed to an ultra-wideband bandwidth of the filter. This new approach increases the coupling effect as well as minimizing the insertion loss in the passband. Experimental results from the simulation are closely agreed to the measured values. In order to prove that the new approach contributes more advantages and viable at the desired application band, the return and insertion losses of the filter were analyzed. Bandpass filters play a significant role in wireless communication systems. Transmitted and received signals have to be filtered at a certain center frequency with a specific bandwidth. In designing of microstrip filters, the first step is to carry out an approximated calculation based on using of concentrated components like inductors and capacitors. After getting the specifications required, we realized the filter structure with the parallel-coupled technique. Experimental verification gives comparison, how close the theoretical results and measurements look like.